BRUXISM - SYMPTOMS, DIAGNOSIS AND TREATMENT- REVIEW - Joel Simon, Christopher; Gayathri; Kumar S, Vinoth; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Bruxism is excessive teeth grinding or jaw clenching. It is an oral parafunctional activity. Etiology of bruxism can be divided into three groups: psychosocial factors, peripheral factors, and pathophysiological factors. Treatment modalities involve occlusal correction, behavioural changes, and pharmacological approaches. Bruxism can occur during wakefulness or during sleep. Bruxism during the daytime is commonly a semivoluntary ‘clenching’ activity and is also known as ‘Awake Bruxism’ (AB) or Diurnal Bruxism (DB). This review was mainly intended to understand the symptoms, diagnosis, and treatment of bruxism.